Calcined sand, stone-like paint and preparation method thereof

By mixing calcined sand with suitable pH and alkalinity with slurry and thickener, imitation stone coating with good storage stability is prepared, which solves the problem of poor storage stability of existing imitation stone coatings and achieves the effect of extending storage time and excellent construction performance.

CN117682784BActive Publication Date: 2025-03-25HEBEI LIONS NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311732297.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-16
Publication Date
2025-03-25
Estimated Expiration
2043-12-16

AI Technical Summary

Technical Problem

During the storage process, existing imitation stone paints are prone to problems such as layering, floating materials, and clumping at the bottom, resulting in poor storage stability and inability to use for a long time.

Method used

A new type of calcined sand with suitable pH is prepared by using calcined sand with a specific ratio of 90-95 parts of round sand, 1-1.8 parts of adhesive and 0.1-0.5 parts of boric acid, and mix it with slurry and thickener to prepare a stone imitation coating with good storage stability.

Benefits of technology

By using calcined sand with appropriate pH, the storage stability of imitation stone coatings is significantly improved, problems such as layering and agglomeration are avoided, storage time is extended, and construction performance is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004610728580000051
    Figure BDA0004610728580000051
  • Figure BDA0004610728580000052
    Figure BDA0004610728580000052
  • Figure BDA0004610728580000061
    Figure BDA0004610728580000061
Patent Text Reader

Abstract

The present application relates to the technical field of architectural coatings, and specifically discloses a calcined sand, a stone-like coating and a preparation method thereof. The present application provides a calcined sand, comprising the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.8 parts of adhesive and 0.1-0.5 parts of boric acid; the present application also provides a stone-like coating prepared using the calcined sand, the stone-like coating comprising the following raw materials in parts by weight: 30-40 parts of slurry, 60-70 parts of calcined sand and 0.1-0.5 parts of thickener. The calcined sand provided in the present application has an appropriate pH value, and the stone-like coating prepared using the calcined sand has good storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of architectural coatings, and in particular to a calcined sand and stone-like coating and a preparation method thereof. Background Art

[0002] Traditional imitation stone paints are divided into real stone paint and multi-color paint. Real stone paint is a paint made by mixing colors with various natural colored sands, while multi-color paint is a single-component paint obtained by suspending two or more water-based colored particles in an aqueous medium. Because the above two paints have realistic imitation marble and granite effects, they are often used as building exterior wall decoration materials.

[0003] However, since both real stone paint and multi-color paint are applied by spraying, it is difficult to control the surface flatness after film formation. In addition, most of the current imitation stone paints have the problem of poor storage stability, that is, the imitation stone paint is prone to stratification after being stored for a period of time, and the rubber material floats and the bottom agglomerates, which makes the imitation stone paint unable to continue to be used, greatly shortening the storage time of the imitation stone paint.

[0004] Therefore, there is an urgent need to provide a stone-like coating with good construction performance and good storage stability to meet the needs of the market. Summary of the invention

[0005] In order to improve the storage stability of stone-like paint, the present application provides a calcined sand, stone-like paint and a preparation method thereof.

[0006] In the first aspect, the present application provides a calcined sand, which adopts the following technical solution:

[0007] The calcined sand comprises the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.8 parts of adhesive and 0.1-0.5 parts of boric acid.

[0008] The present application uses round sand, adhesive and boric acid to prepare a calcined sand, the pH value of the calcined sand is suitable, and the pH value is in the range of 9.8-10.3. The use of the calcined sand to prepare the stone-like paint can significantly improve the storage stability of the stone-like paint, thereby solving the problem of stratification that the stone-like paint is prone to occur during storage in the related art.

[0009] In this application, based on the problem that the stone-like paint in the related art is prone to slurry floating and bottom agglomeration during storage, the inventor of this application conducted research and found that the main reason for this problem is that the alkalinity of the calcined sand is too strong, which destroys the molecular structure of the stone-like paint, thereby causing the stability of the system to deteriorate. Based on this discovery, the inventor prepared a calcined sand with appropriate pH, and used the calcined sand to prepare the stone-like paint. The storage stability of the stone-like paint was significantly improved. It will not agglomerate, mildew, flocculate, etc. when hot-stored at 50°C for 15 days, and the hot storage time can reach more than 20 days.

[0010] Optionally, the calcined sand comprises the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.5 parts of adhesive and 0.1-0.3 parts of boric acid.

[0011] In some embodiments, the weight portion of the adhesive may be 1-1.3 parts, 1-1.5 parts, 1.3-1.5 parts, 1.3-1.8 parts, or 1.5-1.8 parts.

[0012] In a specific embodiment, the weight portion of the adhesive may also be 1 part, 1.3 parts, 1.5 parts or 1.8 parts.

[0013] In some embodiments, the weight portion of the boric acid may be 0.1-0.2 parts, 0.1-0.3 parts, 0.2-0.3 parts, 0.2-0.5 parts, or 0.3-0.5 parts.

[0014] In a specific embodiment, the weight portion of the boric acid can also be 0.1 part, 0.2 part, 0.3 part or 0.5 part.

[0015] Optionally, the concentration of the boric acid is 0.8-1.3 mass %.

[0016] In a specific embodiment, the concentration of the boric acid is 1 mass %.

[0017] Optionally, the calcined sand also includes 0.3-0.8 parts of color powder.

[0018] The present application can obtain calcined sand of different colors by adding color powder to calcined sand, and by controlling the amount of color powder added within the above range, the obtained calcined sand has appropriate color depth and good density.

[0019] Optionally, the pH of the calcined sand is 9.8-10.3.

[0020] The present application adjusts the ratio of round sand, adhesive and boric acid to adjust the pH value of calcined sand to the above range, and uses calcined sand with the above pH value to prepare stone-like paint, which can reduce the damage of calcined sand to the molecular structure of the stone-like paint, effectively avoid the occurrence of hair layer phenomenon of calcined sand, improve the stability of the stone-like paint, and thus extend the storage time of the stone-like paint.

[0021] In a second aspect, the present application provides a method for preparing calcined sand.

[0022] A method for preparing calcined sand comprises the following steps: uniformly mixing various raw materials of the calcined sand, and then calcining at 750-850°C for 15-30 minutes to obtain the calcined sand.

[0023] The present application provides a method for preparing calcined sand. The calcined sand obtained by the above preparation method does not fade, does not bloom, and has good acid and alkali resistance.

[0024] In a third aspect, the present application provides a stone-like paint.

[0025] A stone-like paint comprises the following raw materials in parts by weight: 30-40 parts of slurry, 60-70 parts of calcined sand and 0.1-0.5 parts of thickener.

[0026] The present application prepares a stone-like coating by using the aforementioned calcined sand, slurry and thickener. The stone-like coating has good storage stability. It will not cause problems such as agglomeration, mildew and flocculation when stored at 50°C for 15 days. The 50°C storage time can reach more than 20 days, and it can be stored at room temperature for more than two years. Compared with the stone-like coating in the related art, the pH value of the calcined sand used in the stone-like coating of the present application is within the range of 9.8-10.3. Therefore, the use of the calcined sand to prepare the stone-like coating can avoid the destruction of the molecular structure of the stone-like coating, thereby ensuring the stability of the stone-like coating system.

[0027] The stone-like paint provided in the present application is prepared by mixing a prefabricated slurry, calcined sand and a thickener, and is mainly applied by a batching method. Therefore, compared with the real stone paint and multi-color paint in the related art, the stone-like paint has a good construction effect, a smooth surface after film formation, bright and beautiful colors, excellent physical and chemical properties and 2000h coating aging resistance.

[0028] In some embodiments, the weight parts of the slurry may be 30-35 parts or 35-40 parts.

[0029] In some specific embodiments, the weight parts of the slurry can also be 30 parts, 35 parts or 40 parts.

[0030] In some embodiments, the calcined sand may be present in an amount of 60-65 parts by weight or 65-70 parts by weight.

[0031] In some specific embodiments, the weight proportion of the calcined sand may also be 60 parts, 65 parts or 70 parts.

[0032] Optionally, the stone-like paint further comprises 2.5-4 parts of 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole.

[0033] The present invention can further improve the compatibility between the components of the stone-like coating by adding 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole to the stone-like coating, avoid stratification and flocculation of the stone-like coating, and effectively prolong the storage time of the stone-like coating.

[0034] In some embodiments, the weight of the 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole may be 2.5-3 parts, 2.5-3.5 parts, 3-3.5 parts, 3-4 parts or 3.5-4 parts.

[0035] In a specific embodiment, the weight proportion of the 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole can also be 2.5 parts, 3 parts, 3.5 parts or 4 parts.

[0036] Optionally, the thickener is an acrylic acid alkali swelling thickener.

[0037] Optionally, the slurry comprises the following components in parts by weight: 16 parts of water, 0.2-0.5 parts of cellulose, 0.1-0.3 parts of preservatives, 0.3-0.5 parts of antifreeze agents, 0.1-0.3 parts of defoaming agents, 0.1-0.3 parts of film-forming aids, 0.3-0.5 parts of organic bentonite and 15-20 parts of emulsion.

[0038] In a fourth aspect, the present application provides a method for preparing a stone-like coating.

[0039] A method for preparing a stone-like paint comprises the following steps: adding calcined sand into slurry and stirring evenly; and then adding a thickener to obtain the stone-like paint.

[0040] In summary, this application has the following beneficial effects:

[0041] 1. The present application provides a calcined sand for stone-like paint. The calcined sand has excellent acidity and alkalinity. The use of the calcined sand in the preparation of stone-like paint can effectively avoid the calcined sand from damaging the internal structure of the stone-like paint, ensure the integrity of the molecular structure of the stone-like paint, and thus enable the stone-like paint to obtain an excellent storage time.

[0042] 2. The imitation stone coating provided in the present application has excellent storage stability on the one hand, and the storage time at 50°C can reach more than 20 days. On the other hand, it also has good construction performance, good scraping effect and no flowery phenomenon.

[0043] 3. The present application can further improve the stability of the stone-like paint and extend the storage time of the stone-like paint to more than 30 days by adding 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole to the stone-like paint. DETAILED DESCRIPTION

[0044] In a first aspect, the present application provides a calcined sand, comprising the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.8 parts of adhesive, 0.1-0.5 parts of boric acid, and 0.3-0.8 parts of color powder; further, the calcined sand comprises the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.5 parts of adhesive, 0.1-0.3 parts of boric acid, and 0.3-0.8 parts of color powder. The concentration of boric acid is 0.8-1.3% by mass.

[0045] The preparation method of the calcined sand is as follows: first, add color powder to round sand and mix for 1-2 minutes; then add adhesive and boric acid and mix for 10-15 minutes to obtain a premix; then place the premix in a muffle furnace and calcine at 750-850° C. for 15-30 minutes to obtain calcined sand.

[0046] In a second aspect, the present application provides a stone-like paint, comprising the following raw materials in parts by weight: 16 parts of water, 0.2-0.5 parts of cellulose, 0.1-0.3 parts of preservatives, 0.3-0.5 parts of antifreeze agents, 0.1-0.3 parts of defoamers, 0.1-0.3 parts of film-forming aids, 0.3-0.5 parts of organic bentonite, 15-20 parts of emulsions, 60-70 parts of calcined sand, and 0.1-0.5 parts of thickeners. Further, the stone-like paint also includes 2.5-4 parts of 2-(2'-hydroxy-3', 5'-di-tert-phenyl)-5-chlorobenzotriazole.

[0047] The preparation method of the above-mentioned imitation stone paint is as follows: firstly, water, cellulose, preservative, antifreeze agent, defoamer, film-forming aid, organic bentonite and emulsion are added into a mixer, the mixer is turned on, and the mixture is stirred for 5-10 minutes to obtain a slurry; then, calcined sand is added into the slurry and the mixture is stirred for 5-10 minutes; finally, a thickener is added and the mixture is stirred for 3-5 minutes to obtain the imitation stone paint.

[0048] In the specific embodiment of the present application, the round sand is homogeneous round sand with a specification of 16-30 mesh; the adhesive is purchased from Shenzhen Guolian Adhesive Co., Ltd., model NB-16000; the toner is purchased from Fuzhou Bayer Pigment Co., Ltd.; the CAS number of cellulose is 9004-34-6, purchased from Aladdin; the preservative is purchased from Lonza Group, model BZ-Plus; the antifreeze is ethylene glycol, purchased from Tianjin Guilan Technology Co., Ltd.; the defoamer is purchased from Beijing Qingcai Trading Co., Ltd., model 23654; the film-forming aid is purchased from Qilu Eastman Economic Chemical Co., Ltd.; the organic bentonite is purchased from Hemmings, model BENTONE GS; the emulsion was purchased from Badfu, model RS-706; the thickener was an acrylic acid alkali swelling thickener purchased from Dow Chemical Company, model DR-50; the CAS number of 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 3864-99-1; other reagents, solvents, etc. in this application can also be obtained commercially.

[0049] The present application is further described in detail below in combination with preparation examples, embodiments and performance testing experiments.

[0050] Preparation Example 1-7

[0051] Preparation Examples 1-7 each provide a kind of calcined sand.

[0052] The difference between the above preparation examples is that the addition amount of each raw material is as shown in Table 1 below.

[0053] The preparation method of the calcined sand provided in Preparation Example 1-7 is: first, add color powder to round sand and mix for 2 minutes; then add adhesive and boric acid and mix for 10 minutes to obtain a premix; then place the premix in a muffle furnace and calcine at 800°C for 20 minutes to obtain calcined sand.

[0054] Comparative Preparation Examples 1-5

[0055] Comparative Preparation Examples 1-5 each provide a kind of calcined sand.

[0056] The difference between the above comparative preparation example and preparation example 2 is that the addition amount of each raw material is as shown in the following Table 1.

[0057] Table 1 Addition amount of each raw material in the calcined sand provided in Preparation Examples 1-7 and Comparative Preparation Examples 1-5

[0058]

[0059] Detection test

[0060] The acidity and alkalinity (pH) of the calcined sand obtained in Preparation Examples 1-7 and Comparative Preparation Examples 1-4 were tested, and the results are shown in Table 2 below.

[0061] Detection method: Put 1g of calcined sand into 5mL of water, soak for 15-20min, and then use a pH tester to detect the pH value of the water.

[0062] Table 2 Test results of calcined sand obtained in Preparation Examples 1-7 and Comparative Preparation Examples 1-4

[0063]

[0064]

[0065] Preparation Example 8

[0066] Preparation Example 8 provides a slurry.

[0067] The preparation method of the above slurry is as follows: add 16g of water, 0.3g of cellulose, 0.2g of preservative, 0.4g of antifreeze, 0.2g of defoaming agent, 0.3g of film-forming aid, 0.3g of organic bentonite, and 20g of emulsion into a blender, turn on the blender, and stir for 5 minutes to obtain a slurry.

[0068] Examples 1-7

[0069] Embodiments 1-7 respectively provide a kind of stone-like coating.

[0070] The difference between the above embodiments is that the calcined sand in the stone-like coatings of embodiments 1-7 is derived from preparation examples 1-7 respectively.

[0071] The preparation method of the stone-like coating provided in Examples 1-7 is as follows: 65 g of calcined sand is added to 35 g of slurry (Preparation Example 8), and stirred for 10 min; 0.3 g of thickener is added, and stirred for 3 min to obtain the stone-like coating.

[0072] Comparative Examples 1-5

[0073] Comparative Examples 1-5 respectively provide a kind of stone-like coating.

[0074] The difference between the above comparative examples and Example 2 is that the calcined sand in the stone-like coatings of Comparative Examples 1-5 is derived from Comparative Preparation Examples 1-5, respectively.

[0075] Embodiment 8-11

[0076] Embodiments 8-11 respectively provide a kind of imitation stone coating.

[0077] The difference between the above embodiment and embodiment 2 is that the addition amount of each raw material in the stone-like paint is specifically shown in Table 3 below.

[0078] Table 3 Addition amount of each raw material in the stone-like coating of Examples 8-11

[0079]

[0080] Comparative Example 6

[0081] Comparative Example 6 provides a stone-like paint.

[0082] The difference between the comparative example and Example 2 is that the calcined sand in the imitation stone coating is commercially available (purchased from Guangxi Jinlong Mineral Products Co., Ltd., with a specification of 25-35 mesh spherical sand).

[0083] Examples 12-16

[0084] Examples 12-16 each provide a stone-like paint.

[0085] The difference between the above embodiment and embodiment 2 is that the stone-like paint further includes 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, and the specific addition amount is shown in Table 4 below.

[0086] The preparation method of the above-mentioned imitation stone coating is as follows: add 65g of calcined sand to 35g of slurry (Preparation Example 8), stir for 10min; add 0.3g of thickener and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, stir for 3min, and obtain the imitation stone coating.

[0087] Table 4 Addition amount of 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole in Examples 12-16

[0088]

[0089] Performance Testing The various properties of the stone-like coatings obtained in Examples 1-16 and Comparative Examples 1-6 were tested, and the results are shown in Table 5 below.

[0090] Viscosity: Use Brookfield viscometer 7#30r to detect the viscosity of the stone-like paint.

[0091] Acidity and alkalinity: Use a pH tester to test the pH value of the stone-like paint.

[0092] Construction performance: If there is no difficulty in scraping the imitation stone paint, it is considered as "barrier-free scraping". For specific methods, please refer to JB / T24-2018.

[0093] Thermal storage stability and thermal storage time: seal the imitation stone paint in a glass container, and then put it into a constant temperature box at (50±2)℃. Take it out on the 15th day, cool it down and observe whether the imitation stone paint has abnormal phenomena such as agglomeration, mildew, coagulation and changes in composition. Then put the imitation stone paint back into the constant temperature box, take it out every 2 days for observation, until the imitation stone paint shows abnormal phenomena such as agglomeration, mildew, coagulation and changes in composition, which is the thermal storage time of the imitation stone paint.

[0094] Table 5 Performance test results of stone-like coatings obtained in Examples 1-15 and Comparative Examples 1-6

[0095]

[0096] According to the test results of Table 5, embodiments 1-16 adopt the calcined sand prepared by the present application to prepare the imitation stone coating, and the viscosity of the imitation stone coating obtained is 40000-45000CP, pH is 8-9, the scraping construction process is barrier-free, and the abnormal phenomena such as caking, mildew, cohesion and changes in the composition do not occur in the hot storage for 15 days, and the hot storage time can reach more than 20 days. Although the imitation stone coating obtained by embodiment 10 using commercially available calcined sand has a good construction effect, the hot storage time is only 19 days. Therefore, it is explained that the calcined sand provided by the present application is used to prepare the imitation stone coating, which can further improve the molecular structure stability of the imitation stone coating, and then extend the storage time of the imitation stone coating.

[0097] The test results of Examples 1-7 and Comparative Examples 1-5 show that the viscosity of the imitation stone coating obtained in Examples 1-7 of the present application is 40000-45000CP, the pH is 8-9, and there is no abnormal phenomenon such as caking, mildew, coagulation and changes in composition after 15 days of hot storage, and the hot storage time can be up to more than 20 days. However, the imitation stone coating of Comparative Example 1 is difficult to scrape, and the hot storage time is only 17 days; the hot storage time of the imitation stone coating of Comparative Example 4 is also only 17 days; the imitation stone coating obtained in Comparative Examples 2-3 and Comparative Example 5 has delamination and caking after 15 days of hot storage. Therefore, it is explained that the pH of the calcined sand is controlled between 9.8-10.3 in Preparation Examples 1-7 of the present application, and the obtained imitation stone coating has excellent construction performance and good storage stability.

[0098] Further comparison with Examples 1-7 shows that the thermal storage time of the stone-like coatings of Examples 1-3 and Examples 5-6 can reach 25 days or more. This indicates that the application further controls the amount of adhesive added to between 1-1.5 and the amount of boric acid added to between 0.1-0.3, that is, the pH of the calcined sand is controlled to between 9.9-10.2, and the obtained stone-like coating has better storage stability and longer storage time.

[0099] The test results of Example 2 and Example 12-16 show that the storage stability of the obtained imitation stone coating is further improved by further adding 2-(2'-hydroxy-3', 5'-di-tert-phenyl)-5-chlorobenzotriazole in Example 12-16, and the heat storage time is greater than 27 days; further comparison shows that the heat storage time of the imitation stone coating obtained in Example 12-15 can reach more than 30 days. Therefore, it is explained that the application controls the addition amount of 2-(2'-hydroxy-3', 5'-di-tert-phenyl)-5-chlorobenzotriazole to between 2.5 and 4 parts, which can significantly improve the stability of the imitation stone coating and further extend the storage time of the imitation stone coating.

[0100] In summary, the present application adopts round sand, adhesive, boric acid and colorant to prepare calcined sand, and the pH value of the obtained calcined sand is 9.8-10.3 by controlling the amount of each component within the following range: 90-95 parts of round sand, 1-1.8 parts of adhesive, 0.1-0.5 parts of boric acid and 0.3-0.8 parts of color powder. The calcined sand is used to prepare stone-like paint, and the addition amount of each component of the stone-like paint is controlled within the following range: 30-40 parts of slurry, 60-70 parts of calcined sand and 0.1-0.5 parts of thickener. The obtained stone-like paint has good construction performance and the hot storage time can reach more than 20 days.

[0101] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A stone-like paint, characterized in that: The stone-like paint comprises the following raw materials in parts by weight: 30-40 parts of slurry, 60-70 parts of calcined sand and 0.1-0.5 parts of thickener; The calcined sand comprises the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.8 parts of adhesive and 0.1-0.5 parts of boric acid; the pH of the calcined sand is 9.8-10.

3.

2. The stone-like paint according to claim 1, characterized in that: The calcined sand comprises the following raw materials in parts by weight: 90-95 parts of round sand, 1-1.5 parts of adhesive and 0.1-0.3 parts of boric acid.

3. The stone-like paint according to claim 1, characterized in that: The concentration of the boric acid is 0.8-1.3% by mass.

4. The stone-like paint according to claim 1, characterized in that: The calcined sand also includes 0.3-0.8 parts of color powder.

5. The stone-like paint according to claim 1, characterized in that: The preparation method of calcined sand comprises the following steps: uniformly mixing various raw materials of calcined sand, and then calcining at 750-850° C. for 15-30 minutes to obtain calcined sand.

6. The stone-like paint according to claim 1, characterized in that: The stone-like paint also includes 2.5-4 parts of 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole.

7. The stone-like paint according to claim 1, characterized in that: The thickener is an acrylic acid alkali swelling thickener.

8. The stone-like paint according to claim 7, characterized in that: The slurry comprises the following components in parts by weight: 16-20 parts of water, 0.2-0.5 parts of cellulose, 0.1-0.3 parts of preservatives, 0.3-0.5 parts of antifreeze agents, 0.1-0.3 parts of defoaming agents, 0.1-0.3 parts of film-forming aids, 0.3-0.5 parts of organic bentonite and 15-20 parts of emulsion.

9. The method for preparing the stone-like coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: firstly preparing slurry, then adding calcined sand into the slurry and stirring for 5-10 minutes; and finally adding a thickener and stirring for 3-5 minutes to obtain the stone-like paint.

Citation Information

Patent Citations

  • Batch scraping calcined sand stone-like coating as well as preparation method and application thereof

    CN110563386A

  • Method for producing a colored sand composition, and composition thereof

    US20070137527A1